Characterization of Peatland Soils from the High Andes through 13C Nuclear Magnetic Resonance Spectroscopy - Segnini, A.; Souza, A.A. de; Novotny, E.H.; Milori, D.M.B.P.; Silva, W.T.L. da; Bonagamba, T.J.; Posadas, A.; Quiróz, R. (Wiley, 2013)
Whole soil samples from Peruvian bofedales (highland peatlands), located at an average altitude of 3881 m above sea level, were analyzed through 13C solid-state nuclear magnetic resonance (13C SSNMR) spectroscopy. The objective was to make a semi-quantitative characterization of the predominant organic chemical structures and to compare the organic matter from permanently and seasonally flooded peatlands soils as well as to characterize the changes throughout the soil profile using principal component analysis (PCA) of 13C-SSNMR spectra. Results indicated a relative accumulation of recalcitrant organic compounds as a function of depth that could be due to the constant input of fresh material to the soil surface. Notwithstanding, the results were different for each soil type. In seasonally flooded bofedales, the accumulated recalcitrant material was mainly composed of carboxylated aromatic moieties, whereas in permanently flooded bofedales, the accumulated material presented crystalline polymethylene, being the main difference the anoxic condition of permanently waterlogged soils. On the other hand, the degradable (labile) material was similar in both soils (i.e., mainly cellulose and partially oxidized cellulose). Another interesting feature was that the results seem to corroborate paleobotanical findings, pointing out to an ancient dominance of C4 taxa in Andean grasslands (deep layers in bofedales samples) whose lignin had more coumaryl alcohol at the expense of guaiacyl and syringyl units